The Current knowledge Towards Infective Endocarditis Prophylaxis Among General Dental Practitioners in Zliten-Libya (Journal of Academic Research, 2024)
The aim  of this study  was to evaluate  the knowledge of  general dental practitioners, in private and governmental dental clinics in Zliten, regrading  the current American Heart Association (AHA)  guidelines  for  infective endocarditis prophylaxis.   This surveying  was carried out using a descriptive, closed ended questionnaire which was circulated  among  200 general dental practitioners in private and governmental dental clinics in Zliten-Libya. Data was analysed using SPSS.  The frequency and  percentage of respondents were determined using  a descriptive statistics. The effect of the work sector and professional experience on responses was evaluated using Chi-square test (P < 0.05). The questionnaire  has been completed by 145 general dentists with overall response rate of 72%. The majority of  respondents recommended antibiotic  prophylaxis for prosthetic heart (92.4%) followed by  rheumatic heart disease (89%), mitral valve prolapse (85.5%), history of infective endocarditis attack (84%),  bypass  surgery (76.5%), patient with pacemaker (70.3%) and peripheral vascular grafts with patches (69%). 84% of participants advocated antibiotic prophylaxis for teeth extraction followed by abscess drainage (80%), endodontic treatment (79%) and apicoectomy (64%). 50.7% and 46.2% of respondents identified the correct prophylactic  regimen for patients not allergic and allergic to penicillin, respectively. 60% of participants used multiple antibiotic doses for endocarditis prophylaxis.
Keywords: Infective endocarditic; Antibiotic prophylaxis; Knowledge; Dental practitioners